2011
DOI: 10.3732/ajb.1000151
|View full text |Cite
|
Sign up to set email alerts
|

Seed dormancy in Trillium camschatcense (Melanthiaceae) and the possible roles of light and temperature requirements for seed germination in forests

Abstract: Seeds of T. camschatcense have deep simple double MPD and requirements for radicle emergence: darkness and constant temperatures. Ecologically, edges of forests may be deleterious for germination of the species due to increased light and to higher temperature fluctuations as compared to the interiors of forests. Thus, these specific requirements may play an important role in reducing seed germination of this plant at forest edges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 49 publications
1
38
0
1
Order By: Relevance
“…Intermediate and deep simple MPD are discarded because once the embryo growth occurs, seeds do not need cold exposition to emerge the radicle (Figure 1). Deep simple double MPD can be discarded too, because in this level shoot emergence only occurs after the second winter (Kondo et al, 2011). The embryo growth patterns observed in laboratory trials are corroborated by the phenological tests under closed natural conditions in the non-heated frame shadehouse (Figures 1 and 2).…”
Section: Induction Of Dormancy By Low Temperaturesmentioning
confidence: 59%
“…Intermediate and deep simple MPD are discarded because once the embryo growth occurs, seeds do not need cold exposition to emerge the radicle (Figure 1). Deep simple double MPD can be discarded too, because in this level shoot emergence only occurs after the second winter (Kondo et al, 2011). The embryo growth patterns observed in laboratory trials are corroborated by the phenological tests under closed natural conditions in the non-heated frame shadehouse (Figures 1 and 2).…”
Section: Induction Of Dormancy By Low Temperaturesmentioning
confidence: 59%
“…Embryos in seeds of Melanthiaceae have been observed to be small in relation to the size of the endosperm (Baskin and Baskin, 1988;Baskin et al, 2001;Kondo et al, 2011). In Trillium camschatcense, seeds had underdeveloped embryos at dispersal and took more than 1 year before radicle emergence occurred in the field conditions, and were therefore classified as having MPD (Kondo et al, 2011). It has also been observed that seeds of several species such as T. flexipes, T. sessile (Baskin and Baskin, 1988), and Chamaelirium luteum (Baskin et al, 2001) had MPD.…”
Section: Introductionmentioning
confidence: 92%
“…According to Baskin and Baskin (1998), rudimentary or small, linear embryos must elongate before germination occurs; thus, the seeds generally are referred to as having underdeveloped embryos. Previous studies showed that seeds of Melanthiaceae had small, underdeveloped embryos (Baskin and Baskin, 1988;Baskin et al, 2001;Kondo et al, 2011;Martin, 1946 Seeds of H. koreana and H. tubiflora were collected on 20 May 2012 and 18 June 2012, respectively, and soaked in 0, 10, 100, or 1,000 mg・L -1 GA3 for 24 h at room temperature before incubation at 15/6°C and 25/15°C in a 12-h light/dark photoperiod. In H. koreana, seeds collected on 6 June 2013 were incubated at constant 25°C, placed on filter paper (Whatman No.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…백합과의 Erythronium japonicum (Kondo et al, 2002), E. grandiflorum (Martin, 1946), Trillium camschatcense (Kondo et al, 2011), 그리고 미나리 아재비과의 Helleborus niger (Niimi et al, 2006), Hepatica nobilis (Nomizu et al, 2004), Aconitum lycoctonum ( 등에서 이에 대한 연구가 진행되고 있다 (Lee et al, 2003(Lee et al, , 2011(Lee et al, , 2012Rhie et al, 2010 (Walk et al, 1999). Pericarp in seeds of three Thalictrum species and caudal appendage in seeds of two Heloniopsis species were not included for calculating E:S ratio.…”
Section: 온대지방에 자생하는 많은 백합과(Liliaceae)와 미나리아 재비과(Ranunculaceae) 식물들은 미mentioning
confidence: 99%